Sessantotto - L'utopia della realta . 68 - Utopia of Reality - Orgnani, Ferdinando Vicentini (Italy, 2006)
Duration: 01:30:00 Sessantotto. L'utopia della realtà based upon the script by journalist Adalberto Baldoni, is an attempt to supply answers to the questions raised by the 1968 phenomenon in Italy within a transnational perspective. The documentary starts with a presentation of the Beat Generation (Ginsberg, Kerouac) and ends with the portrayal of the protest movement based in Rome. The central thesis of the film is that the escalation of violence in the 70s and 80s resulted from the “strategia degli opposti estremi”, an instumentalised polarisation of the anti-authoritarian conflict of ‘68.